Violence in Schools: Perspectives (and hope) from Galtung and Buber. Issue 11 (18th September 2016) - Cremin, Hilary; Guilherme, Alexandre
Abstract: Research into violence in schools has been growing steadily at an international level, and has shown high degrees of violence at various different levels. Given the seriousness of the problem, finding ways of responding to this issue in schools becomes an imperative for educationists. In this article, we engage with this problem by defending the view that whilst violence might be endemic in schools, there are also real possibilities for working towards different ways of being in relationship in schools. Firstly, we discuss Galtung's understanding of violence and peace, paying particular attention to his concepts of structural and cultural violence, peacekeeping, peacemaking and peacebuilding . Secondly, we connect Galtung's notions of peacemaking to Buber's philosophy of dialogue, in order to make a case for an 'epistemological shift' which might enable individuals and communities to achieve 'peace'. Finally, we direct our argument to the education context and put forward some concrete proposals for peacemaking in schools.